2020
DOI: 10.1021/acs.cgd.9b01572
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Solvent Effect on Crystal Growth of Energetic Materials for Accurate Morphology Prediction

Abstract: A new strategy for the accurate morphology prediction of energetic material crystals was proposed in the theoretical framework of the attachment energy model; namely, the “averaged” attachment energies are replaced by the binding energies at the adsorption sites that were found by computational simulations to be the crucial factor to determine the crystal growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The simulation with this occupancy model (OM) shows a similar result to that in ref . In a recent theoretical work by Yingzhe Liu and coauthors, the attachment energies in the AE model were replaced by the binding energies at the adsorption sites on the crystal faces to predict the morphology of HMX in acetone. The results revealed that the (101̅) and (101) planes were absent from the crystal surface.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The simulation with this occupancy model (OM) shows a similar result to that in ref . In a recent theoretical work by Yingzhe Liu and coauthors, the attachment energies in the AE model were replaced by the binding energies at the adsorption sites on the crystal faces to predict the morphology of HMX in acetone. The results revealed that the (101̅) and (101) planes were absent from the crystal surface.…”
Section: Resultssupporting
confidence: 70%
“…The AE model is based on a simple assumption that the crystal facet growth rate in the solvent environment is proportional to the attachment energy, which is calculated from the energy difference between the solute–crystal and the solvent–crystal interactions. This model has been applied in the crystal habit study of many EMs, such as CL-20, HMX, and RDX. More recently, Yingzhe Liu and coauthors have developed a new strategy for the accurate morphology prediction of energetic material, in considering the binding energies of the solvent at the adsorption sites on different crystal planes . Besides, other models, e.g., occupancy model (OM), spiral growth model (SG), and 2D nucleation model, have been developed and applied to the simulation of the grown crystal morphology of EMs in solvent. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Lan et al predicted the crystal morphologies of hexanitrohexaazaisowurtzitane (CL‐20) in different solvents 11 . Liu et al considered the interaction between the solvent and crystal surface of the interface binding site and accurately predicted the crystal morphology of 1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocane (HMX) in acetone (AC) solvent 12 . However, the prediction of H 4 TTP crystal morphology has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…From the above analysis, it could be said that the structure of the interface has reached a stationary state in this simulation time, and the structural and energetic analysis could be performed during the final 500 ps of the simulation time. Moreover, during this simulation time, the local solvent densities of the interfacial models fluctuate weakly and approach the bulk solvent density, while the water solvent molecules move away from the crystal faces, as shown in Figure S11. ,, The mean solvent densities which are along the normal to the crystal faces at its plateau of (1 0 1̅)/solvent, (1 0 1)/solvent, (0 0 2)/solvent, (0 1 1)/solvent, (0 1̅ 1)/solvent, (1 1̅ 0)/solvent, (1 1 0)/solvent models are 0.986, 0.985, 0.981, 0.987, 0.989, 0.979, and 0.980 g/cm 3 , respectively, which are close to the simulated bulk density of the water solvent bulk (0.989 g/cm 3 ). Therefore, the behaviors of the simulations are physically consistent.…”
Section: Resultsmentioning
confidence: 99%